ZBP1 promotes LPS-induced cell death and IL-1β release via RHIM-mediated interactions with RIPK1 - Muendlein, Hayley I. (Nat Commun, 2021)
Inflammation and cell death are closely linked arms of the host immune response to infection, which when carefully balanced ensure host survival. One example of this balance is the tightly regulated transition from TNFR1-associated pro-inflammatory complex I to pro-death complex II. By contrast, here we show that a TRIF-dependent complex containing FADD, RIPK1 and caspase-8 (that we have termed the TRIFosome) mediates cell death in response to Yersinia pseudotuberculosis and LPS. Furthermore, we show that constitutive binding between ZBP1 and RIPK1 is essential for the initiation of TRIFosome interactions, caspase-8-mediated cell death and inflammasome activation, thus positioning ZBP1 as an effector of cell death in the context of bacterial blockade of pro-inflammatory signaling. Additionally, our findings offer an alternative to the TNFR1-dependent model of complex II assembly, by demonstrating pro-death complex formation reliant on TRIF signaling.